Distribution Automation Effects on Reliability During Major Contingencies - Yoldaş, Yeliz; Onen, Ahmet; Alan, İrfan; Broadwater, Robert P. (IEEE Computer Society help@computer.org, 2018)
Distribution automation affects reliability by providing faster restoration ability. In this study, the effect of distribution automation on radial distribution circuits during substation failures at peak load is investigated. The ultimate goal is to compare circuit automation to manual operation, where the comparison evaluates planning criteria reliability for customer interruption hours. The results show that distribution automation can improve reliability measurements such as SAIDI, SAIFI and CAIDI. © 2018 Elsevier B.V., All rights reserved.
Elektroinstitut Milan Vidmar (EIMV); ELES - Prenasamo Energijo Ohranjamo Ravnovesje; et al.; Kolektor; MR; TDK
Yoldas, Yeliz/0000-0002-9821-9339; Onen, Ahmet/0000-0001-7086-5112
Keywords: Distribution Automation; Power System Reliability; System Reconfiguration; Automation; Customer Interruptions; Distribution Automation; Manual Operations; Planning Criteria; Power System Reliability; Radial Distributions; Reliability Measurements; System Reconfiguration; Reliability